Jewish Persecution and Mimetic Rivalry in the Iberian Kingdoms of Aragon and Castile - Emilio Moreno Villanueva (Biblos)
This article applies René Girard’s mimetic theory to analyze the escalation of violence against Jews in medieval Iberia during the fourteenth and fifteenth centuries. It explores how economic, social, and religious factors fueled a mimetic crisis, leading to the scapegoating and eventual expulsion of Jews in 1492. The study highlights the importance of the "other" in constructing collective identities and scapegoats, particularly in the context of religious minorities like the Jews in medieval Iberia. Through Girard’s framework, the analysis highlights the dynamics of mimetic desire and mediation, offering insights into the interplay of violence, identity, and power in medieval societies.